2016
DOI: 10.1177/2333721416630492
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Older Adults

Abstract: Objective: The objective of this review was to assess published literature relating to health literacy and older adults. Method: The current review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta Analyses. Results: Eight articles met inclusion criteria. All studies were conducted in urban settings in the United States. Study sample size ranged from 33 to 3,000 participants. Two studies evaluated health-related outcomes and reported significant associations between low h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
230
1
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 279 publications
(251 citation statements)
references
References 39 publications
7
230
1
13
Order By: Relevance
“…Multiple health literacy assessment tools have been identified for older adults (Chesser, Keene Woods, Smothers, & Rogers, 2016). In addition, there is some evidence that results from a three-question screener or a single item screening (SIS) tool may be comparable (valid and reliable) with longer assessments to identify individuals with low health literacy (Bishop et al, 2016; Chew et al, 2008; Quinzanos, Hirsh, Bright, & Caplan, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple health literacy assessment tools have been identified for older adults (Chesser, Keene Woods, Smothers, & Rogers, 2016). In addition, there is some evidence that results from a three-question screener or a single item screening (SIS) tool may be comparable (valid and reliable) with longer assessments to identify individuals with low health literacy (Bishop et al, 2016; Chew et al, 2008; Quinzanos, Hirsh, Bright, & Caplan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is some evidence that results from a three-question screener or a single item screening (SIS) tool may be comparable (valid and reliable) with longer assessments to identify individuals with low health literacy (Bishop et al, 2016; Chew et al, 2008; Quinzanos, Hirsh, Bright, & Caplan, 2015). However, no single study has reported the validation of health literacy assessment tools for use in an older adult population (65 years of age or older) (Chesser et al, 2016). The purpose of this study was to assess health literacy rates and validate a SIS health literacy tool for adults aged 65 years and older.…”
Section: Introductionmentioning
confidence: 99%
“…4 As a result of their high use of healthcare services and medication, older adults are an especially frail population that requires specifically designed health literacy screening tools, as highlighted in a recent systematic review. 5 The floor-effect identified when assessing health literacy with the NVS in older patients hampers its predictive power as a proxy for poor health outcomes and poor medication selfmanagement capacity. Thus, we do not recommend that researchers and clinicians in Portugal use the NVS when assessing health literacy of older adults in clinical practice.…”
Section: Quantas Revistas De Psiquiatria Temos Em Portugal? No íNdex mentioning
confidence: 99%
“…Therefore, factors beyond geographic location influence limit rural adults' eHealth use. Considering limited empirical evidence about the eHealth literacy of rural populations [14], future research is needed to explore eHealth literacy and its measurement among populations according to rurality in regard to physical space (i.e., RUCA or MSA data) and sociocultural rural identity.…”
Section: Limitationsmentioning
confidence: 99%
“…Older adults generally have lower health literacy than their younger counterparts [14,15], yet this population is increasingly adopting the Internet with a high degree of confidence to access health information and supplement their healthcare [4,12]. Older adults also tend to have unique health needs as compared to younger adults [16,17].…”
Section: Introductionmentioning
confidence: 99%